Conduction block and temporal dispersion in a SIGMAR1‐related neuropathy. Issue 4 (1st November 2022) - Frezatti, Rodrigo Siqueira Soares; Tomaselli, Pedro José; Figueiredo, Fernanda Barbosa; Zuchner, Stephan; Reilly, Mary M; Marques, Wilson
Abstract: The distal hereditary motor neuropathies (dHMN) encompass a group of peripheral nervous system disorders characterized by progressive distal predominant weakness and wasting, usually in a length‐dependent pattern. The classical neurophysiological pattern is a motor axonal neuropathy with chronic distal denervation/reinnervation on needle examination. Conduction block (CB) and temporal dispersion (TD) are electrophysiological features classically associated with acquired demyelinating neuropathies. Although they have rarely been reported in hereditary neuropathies, to date they have not been described in dHMN. We report a sporadic case of a patient with neurophysiological criteria consistent with multifocal motor neuropathy with CB (MMN) refractory to immunomodulation. WES revealed a homozygous nonsense pathogenic variant in sigma nonopioid intracellular receptor‐1 gene ( SIGMAR1 ). SIGMAR1 ‐related disorders have been reported with distinctive features suggesting it is not a typical length‐dependent neuropathy. Nevertheless, CB and TD are unexpected and as far as we have known not been described previously in such patients. This case expands the neurophysiological spectrum of this disease and alerts clinicians to this acquired demyelinating motor neuropathy mimic.